(untitled) (Management and Connections Journal, 2022)
The academic management of Federal Institutions of Higher Education is characterized by the professor acting as manager, and involves facing many challenges. The objective of this research is to understand the managerial challenges faced by professors as Undergraduate Course Coordinators in a Federal Institution of Higher Education. The research is characterized as qualitative and field research, with a descriptive approach. A semi-structured interview script was used with the interviewees and the procedures adopted to treat and interpret the research data were carried out through content analysis. The results indicate that the main challenges faced by coordinators include: lack of financial resources; interpersonal relationship with professors; conflict conciliation; dealing with student problems; conciliate all managerial and academic activities; make changes in the Pedagogical Project of the Course and in the curriculum of the course; manipulate the tools in the SIGAA, SIPAC systems.